Quality of life in women with vulvar cancer submitted to surgical treatment: a comparative study - de Melo Ferreira, Ana Paula [UNESP]; de Figueiredo, Elyonara Mello; Lima, Renilton Aires; Candido, Eduardo Batista; de Castro Monteiro, Marilene Vale; Rossi de Figueiredo Franco, Telma Maria; Traiman, Paulo [UNESP]; da Silva-Filho, Agnaldo Lopes (Elsevier B.V., 2012)
Objectives: To investigate the occurrence and severity of lymphoedema of the lower extremities (LLE), quality of life (QoL), and urinary and sexual dysfunction in women with vulvar cancer submitted to surgical treatment.Study design: Twenty-eight patients with vulvar cancer submitted to vulvectomy and inguinofemoral lymphadenectomy and 28 healthy, age-matched women (control group) were evaluated. The occurrence and severity of LLE were determined by Miller's Clinical Evaluation. QoL, urinary function and sexual function were assessed by the EORTC QLQ-C30, SF-ICIQ and FSFI questionnaires, respectively. The differences between groups and correlations were assessed using Student's r-test, Chi-squared test, Mann-Whitney U-test and Spearman's rho test.Results: The groups were similar in terms of marital status, educational status, menopausal status, hormone therapy and height. The occurrence and severity of LLE were higher in women with vulvar cancer compared with the control group (p < 0.001 and p = 0.003, respectively). A significant association was found between the severity of LLE and advanced age (p = 0.04), and the severity of LLE and higher body mass index (BMI; p = 0.04) in patients with vulvar cancer. In the patients with vulvar cancer, there was a significant correlation between the severity of LLE and worse QoL in the following domains: physical, cognitive, emotional, social, fatigue, pain, sleep and financial questions (p < 0.05). There was no difference in urinary function between the two groups (p = 0.113). Age and number of deliveries were the only variables associated with the occurrence of urinary incontinence (p = 0.01). Urinary incontinence was present in women with a mean age of 74.9 +/- 4.6 years and a mean of 7.3 +/- 1.3 normal deliveries. There was no difference between the groups in terms of the sexual function. Multivariate analysis showed an association between sexual function and age (p = 0.01), and sexual function and being in a stable relationship (p = 0.02).Conclusion: Patients submitted to vulvectomy or inguinofemoral lymphadenectomy for vulvar cancer are at higher risk of developing LLE compared with healthy, age-matched women. This has a negative effect on QoL, but does not interfere with urinary or sexual function. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Vulvar cancer; Vulvectomy; Inguinofemoral lymphadenectomy; Lymphoedema; Urinary incontinence; Sexual dysfunction; Quality of life